Desafíos de la enseñanza y aprendizaje en el área de Lengua y Literatura durante la pandemia por Covid-19 en el tercero bachillerato de la Unidad Educativa “Pedro Vicente Maldonado”, período 2022 - Rojas Guevara, Jaime Andrés (2023)
This research aims to propose strategies to face the challenges of teaching and learning in the area of Language and Literature during the pandemic in the third baccalaureate of the "Pedro Vicente Maldonado" Educational Unit, period 2022. A quantitative approach is used with a field research type, non-experimental design because the variables the students showed were not manipulated, its scope was descriptive. The technique used was the survey with a questionnaire to 36 students who made up the study population. The information gathered made it possible to identify knowledge gaps in certain topics such as homophone words, Hispanic American narrative, and diglossia. Therefore, the proposed strategies will help reinforce these identified gaps so that the teaching-learning process will be developed adequately, fulfilling all curricular objectives.